Current situation and prospects of the quinoa sector in Bolivia - Rubén Collao Pérez; Beatriz Muriel Hernández (Institute for Advanced Development Studies (INESAD), 2024)
We analyze the quinoa sector situation and prospects in Bolivia, based on both secondary and primary information sources (i.e. surveys of producers and interviews to key actors). The quinoa sector has sustainability problems in production, market shares and price volatility. However, this grain - specifically the royal quinoa from the Southern Altiplano - has great potential to remain in the world market within niches that value organic or regenerative production, as well as to increase national consumption. In this regard, we believe that it is necessary to impulse the quinoa transformation with greater diversification, productive complementation and coordination between the various stakeholders. In this productive dynamics, small quinoa producers can insert themselves into the value chain, which requires the strengthening of their hard and soft skills, as well as greater technical assistance. Finally, the quinoa sector sustainability requires a comprehensive approach that includes good agricultural practices caring the environment, as well as more conscious consumption.
Keywords: D29; Q11; Q19; Q59; 330; quinoa; quinoa value chain; Bolivia